Philadelphia Paper - The Fire Clays and Associated Plastic Clays, Kaolins, Feldspars, and Fire Sands of New Jersey - John C. Smock (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1879)
The fire-clays of New Jersey belong in two geological ages, the cretaceous and quaternary, or post-tertiary. Three very small deposits of plastic clays have been discovered within the limits of the Archæan rocks. These are not refractory and of little importance, excepting in a geological consideration. They have resulted from a decomposition of the feldspars of the rock in situ, and they have been classified as inferior kaolins.